Water stewardship and business value creating abundance from scarcity - Sarni, William; Grant, David (Earthscan water text series, 2018)
The tangible value of increased water efficiency, reuse and recycling and improved social license to operate are moving more companies to adopt water stewardship strategies. This book frames an expanded strategy for water stewardship and business value creation, including brand value, that benefits a range of stakeholders including consumers, customers, investors and employees. The book established the linkages and value from an integrated water and business strategy and an approach for companies to follow.